Padshahnama: A Chronicle of the Reign of Shahjahan (Volume 2: 1637–1647) - W. M. Thackston, Abdul-Hamid Lahauri Edited and Translated by. author. aut Link
IX, 747 p. 2 illus., 1 illus. in color.
Keywords: This work—divided across three volumes—chronicles three decades of the reign of the Mughal Emperor Shahjahan (1628–1658). The first two volumes are by Abdul-Hamid Lahauri, and the third volume, available for the first time, is by Muhammad Waris. Since it is a court chronicle, the emphasis throughout is on the rise and fall of courtiers, governors, administrators, and military commanders and on incessant military campaigns in the Deccan, Bengal, and Afghanistan, but valuable details of life at court and the architecture of one of India’s most avid builders are also included. This is an indispensable resource for students and scholars of Mughal India as well as those interested in Persian and Iranian studies.